PkM REVITALISASI POSYANDU DI DESA BORRISALLO KABUPATEN GOWA - Hamzah, Wardiah; Sartika, Sartika; Syam, Nasruddin (Jurnal BALIRESO, 2018)
The revitalization of Posyandu is aimed to improve the function and performance of Posyandu,with the main activities of training, service and community movement. Facilities andinfrastructure in Posyandu Melati I are not adequate, active cadres are 4 people, communityparticipation in utilizing posyandu about 45%, about 2% of children with less nutrition. Theactivities carried out in the form of procurement of facilities and infrastructure improvements,facilitate training of posyandu cadres, supplementary feeding and nutritious food and wormcounseling for mother with toddlers. Procurement of facilities and infrastructure in the form of 9types of equipment required Posyandu Melati I. Coordination to Puskesmas Parangloe producestraining activities posyandu cadres planed in October 2017. Supplementary feeding og green beanporridge, on approximately 30 children under five. Nutrition food and worm counseling attendedas many as 15 mothers who have a toddler. Pre-Post test evaluation were conducted before andafter the extension materials were given, indicating an increase in extension counseling knoeledgefrom 43% to 89%. Posyandu Cadres are also advised to actively invite community to be willing tovolunteer posyandu cadres, providing additional foods of varying kind so that toddler do not getbored ang eager to come to posyandu every month. Provision of nutritional material should beaccompanied by a food model and posyandu should have a storage cabinet of goods.